Exploring regional disparities and stakeholder engagement in Slovenian EIP-AGRI projects - Mikolič, Sara (Revija za geografijo, 2025)
The European Innovation Partnership for Agricultural Productivity and Sustainability (EIP-AGRI) was introduced to enhance EU’s capacity for agricultural innovation by bridging the gap between research and practise. This paper explores the implementation of EIP-AGRI Operational Groups in Slovenia, focusing on spatial distribution, stakeholder networks, and thematic priorities. Findings indicate that farmers often take a passive role in innovation processes. Strengthening their role as co-creators could improve applicability impact. Environmental sustainability and climate adaptation are key thematic priorities, but project selection remains administratively driven rather than reflecting stakeholder needs. A higher concentration is found in the Eastern and Central Slovenia, likely due to agriculture’s role, farm density, as well as support networks, including educational, research institutions and advisory services.
Keywords: agricultural innovation; EIP-AGRI Operational Groups; EIP-AGRI operativne skupine; innovation and agricultural policies; inovacijske in kmetijske politike; kmetijske inovacije; multi-actor networks; večdeležniški projekti